The Conditional Probability of Vestibular Schwannoma Growth at Different Time Points After Initial Stability on an Observational Protocol. Issue 2 (February 2020) - Sethi, Mantegh; Borsetto, Daniele; Cho, Yeajoon; Gair, Juliette; Gamazo, Nicola; Jefferies, Sarah; Joannides, Alexis; Mannion, Richard; Helmy, Adel; Axon, Patrick; Donnelly, Neil; Tysome, James R.; et al.
Abstract : Objective: The natural history of vestibular schwannomas (VS) is well documented in the literature, with tumour growth being paramount to decision making for both surveillance and treatment of these patients. Most previous studies refer to the risk of VS growth over a given period of time; however, this is not useful for counselling patients at different stages of their follow-up, as the risk of tumour growth is likely to be less following each subsequent year that a tumour does not grow. Accordingly, we investigated the conditional probability of VS growth at particular time-points, given a patient has not grown thus far. This Bayesian method of risk stratification allows for more tailored and accurate approximations of the risk of growth versus nongrowth of VS. Methods: Retrospective analysis of a prospectively collected database in a tertiary referral skull base unit, containing all patients diagnosed between 2005 and 2014 with sporadic unilateral VS and a minimum of 5-year surveillance. Results: A total of 341 patients met the inclusion criteria. The mean age at diagnosis was 67 years, the sizes of the VS at diagnosis were intracanalicular in 49%, small in 39%, medium in 11%, and large in 1%. Over the entire 5-year surveillance period, a total of 139 tumours were seen to grow (41%) and 202 did not grow (59%). At 1 year, the probability of growth given that the tumour had not grown to date was seen to be 21%, at 2 years 12%, at 3 years 9%, at 4 years 3%, and at 5 years 2%. The conditional probability of growth of extracanalicular VS was significantly higher in the first year when compared with intracanalicular VS (29% versus 13%, p = 0.01), but there was no such difference in years 2, 3, 4 or 5 ( p = 0.60, 0.69, 0.36, 0.39, respectively). Conclusion: This is the first study in the literature concerned specifically with the conditional probability of VS growth. The data presented here can be used to better inform VS patients of their risk of growth at particular time points in their disease—the longer VS have been observed to be stable, the lower the risk of subsequent growth in a given year. Further, an extracanalicular vestibular schwannoma is more likely to grow in the first year compared with an intracanalicular vestibular schwannoma. Our data also adds support to surveillance protocols with increasingly infrequent MRI scans, as after 4 years of not growing, the risk of growth in year 5 falls to <2%.